EVALUATION THREE SCINTILLATORS USED FOR ACTIVITY - Rahmawati Rahmawati; Alfian Noor; Maming maming; Muhammad Zakir (Marina Chimica Acta, 2015)
Three scintillators, ultimagold, aqualight, and aquasol, have been applied to compare performance of liquid scintillation counter upon its C-14 activity measurement in biodiesel supplied by Pertamina in Makassar. The results showed that efficiency of aquasol is lower(0.2), while aqualight and ultimagold is higher (> 0.5). However eff iciency stability of ultimagold is considered better. It can be concluded that using ultimagold may provide more efficient and stable result and consequently more suitable as scintillator.